Assessing the General Health System of Cyprus: a questionnaire analysis based on public perception - George Evripides; Paul Christodoulides (Archives of Public Health)
Abstract A medical health system (MHS) can be viewed as a diverse network of organizations, experts, and resources devoted to promoting, maintaining, and restoring health and well-being in people and societies. There are numerous MHS throughout the world, and their success depends on a number of aspects that should be met. One such MHS is the newly established General Health System (GHS) of Cyprus, a blend of national HS and Social Health Insurance, supported by beneficiaries, employers, and the state. Following the results of a recent study, based on the same questionnaire, the aim of the present study is to attempt a further assessment on how the various factors (constructs) and demographic variables of people of Cyprus interact in their view of the GHS. The questionnaire was constructed on the basis of the available literature and the information gathered about MHS and their features. It includes 5-point Likert-scale items reflecting relevant factors such as Satisfaction (SAT), Trust (TRU), Reliability (REL), Expectations (EXP), Improvement factors (IMP), and Comparison of the Cyprus Health System before and after the implementation of GHS (COM), and others. The questionnaire was completed by 445 individuals in all districts of Cyprus between January and March of 2024. The descriptive statistics analysis of the questionnaires led to useful findings such as the particularly low mean values for the constructs of SAT, TRU and REL. Another finding is that there is not much variation in the mean values among the categories of groups such as gender, age, education level, annual income, work sector, and residence district. To this end an Analysis of Variance, followed by a multiple regression analysis on all constructs was done, in order to clarify/verify certain issues, which led to conclusions that can be used for the amelioration of the GHS. Demographic variables such as age group and income level have influences on all constructs mentioned above and must be tackled differently by GHS stakeholders. There is a strong correlation between SAT, TRU and REL and COM meaning that if one aims to make reforms on GHS targeting higher SAT, they should enhance TRU, REL, and COM.